Comparative Analysis of UV-assisted Removal of Azithromycin and Cefixime from Aqueous Solution Using PAC/Fe/Si/Zn Nanocomposite - Azadeh Mehrdoost; Reza Jalilzadeh Yengejeh; Mohammad Kazem Mohammadi; Ali Akbar Babaei; Azadeh Haghighatzadeh (Shiraz University of Medical Sciences, 2021)
Background: Pharmaceutical pollutants are one of the most important pollutants for water resources, and their health and environmental effects have been well estimated.Absorption is one of the best methods of the removal of antibiotics using nanocomposite. Methods: This experimental study was performed on Nano composites. The PAC/Fe/Si/Zn Nano composite was successfully synthesized using a co-precipitation method in which iron (Fe), silicon (Si) and zinc (Zn) were loaded on the activated carbon powder (PAC). The structural features of the as-synthesized Nano composite were determined using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectroscopy (EDS). The as-synthesized Nano composite was utilized to remove azithromycin and cefixime from aqueous solution with the assistance of UV light. The effect of operational parameters such as pH, irradiation time, initial azithromycin/cefixime concentration and Nano composite dose on UV-assisted removal performance was evaluated using an optimization process. Results: The UV-assisted removal activities indicated more removal percentage (99.7%) for azithromycin compared to cefixime (95.6%). The kinetics of removal was tested using Langmuir-Hinshelwood model, indicating the first-order reaction kinetics as the best model for UV-assisted removal of both azithromycin and cefixime. Adsorption equilibrium data were modeled using Langmuir and Freundlich isotherms. Azithromycin equilibrium adsorption showed a good fit with both Langmuir and Freundlich models, while the most suitable model for cefixime adsorption was estimated to be Langmuir isotherm.  Conclusion: The findings showed that PAC/Fe/Si/Zn Nano composite were well able to degrade non-biodegradable antibiotics in aqueous solutions, which is very valuable from environmental aspects.